Panel-based NGS reveals disease-causing mutations in hearing loss patients using BGISEQ-500 platform. Issue 12 (March 2019) - Sun, Yan; Yuan, Jing; Wu, Limin; Li, Min; Cui, Xiaoli; Yan, Chengbin; Du, Lique; Mao, Liangwei; Man, Jianfen; Li, Wei; Kristiansen, Karsten; Wu, Xuan; et al.
Abstract : Abstract: Hearing loss is a highly heterogeneous disease presented with various phenotypes. Genetic testing of disease-causing mutations plays an important role in precise diagnosis and fertility guidance of heredity hearing loss. Here we reported an effective method employing target enrichment and BGISEQ-500 platform to detect clinically relevant alterations for heredity hearing patients in a single assay. In this study, we designed an array based chip, containing 127 genes related to hearing loss. Then we conducted targeted next-generation sequencing toward 58 patients to make a precise diagnosis using BGISEQ-500 platform. We successfully detected disease-causing mutations in 77.59% (45/58) of the patients with hearing loss. Finally, a total of 62 disease-causing mutations were identified, including 31 missense, 17 Indel, 11 splicing, 2 synonymous, and 1 copy number variant. 58.06% (36/62) of which has never been reported before. To our knowledge, this is the first report using BGISEQ-500 platform to investigate both syndromic and nonsyndromic hearing loss in the Chinese population. The results showed that this method can greatly assist and enhance hearing loss diagnosis and improve molecular diagnostics outcome. Abstract : Supplemental Digital Content is available in the text